Entrepreneurship education programs in Malaysian polytechnics. Issue 7 (8th August 2016) - Othman, Norasmah; Nasrudin, Norfadhilah
Abstract : Purpose: – The purpose of this paper is to evaluate students' views on the on-the-campus entrepreneurship programs in Malaysian polytechnics. Participation in the entrepreneurship programs is able to stimulate an interest in entrepreneurship, and improve the knowledge, skills, and entrepreneurial experience of its students. Design/methodology/approach: – This study adopted a survey method designed in the form of an objective-oriented program evaluation. Questionnaires were used to identify the students' level of assessments of the instructional dimensions. This study explored the differences in evaluation based on gender, specializations, and courses attended. Findings: – The results showed moderately high level of evaluation. The analysis of gender differences shows that gender did not affect students' views on the instructional dimension. However, students' specialization and courses attended are associated with significant differences in the level of evaluation. Research limitations/implications: – This research is limited to only five Malaysian polytechnics. The study was looking into the instructional dimension of the entrepreneurship programs. Further research should include the assessment of the institutional side of the programs. Practical implications: – The evaluation results provide important recommendations to improve some practical aspects of the entrepreneurial activities. The polytechnics' departments can focus on the actual content as well as on the learning experience to implement conducive, positive, and supportive practices that could lead to a maximum participation rate among students. Social implications: – Increase the number of students involved in entrepreneurship. Originality/value: – There have been no discussions or evaluation of the entrepreneurship programs conducted in Malaysian polytechnics in terms of objective-oriented evaluation. This paper attempts to fill the current gap.